If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2=3(x-5)+1-2x
We simplify the equation to the form, which is simple to understand
2=3(x-5)+1-2x
Reorder the terms in parentheses
2=+(+3x-15)+1-2x
Remove unnecessary parentheses
+2=+3x-15+1-2x
We move all terms containing x to the left and all other terms to the right.
-3x+2x=-15+1-2
We simplify left and right side of the equation.
-1x=-16
We divide both sides of the equation by -1 to get x.
x=16
| 3b+17=29 | | 5(2x-7)+42-3x=2 | | 17k=5k-2 | | 10(-10)=0 | | 3x-x+10-12=-188 | | 42.72=.99+x | | 0.4(-0.04-7x)=-2.7x | | 12x-6x=36 | | 5z+2=17 | | -29-10n=-18n+9 | | a=x | | -4n+3=13 | | 14x+23=4x+173 | | 11-2x+8x+5=32 | | r+1/3=8/3 | | (x^2-2x)-180=0 | | 9=g+3 | | -(12-4x)+8(10-4x)= | | 34=t+15 | | x-5/3=10 | | 5(3x-4)+2=4(3x+2) | | 7+8x=98.2 | | -2/5y=-4/15 | | 15.99x-26.73=42.72 | | 0.05s+0.10(6000-s)=375 | | x+2=4(4x-6) | | 3x-5=1x-13 | | 7*0+8y=7 | | 6x^2+2x+2=150 | | 0.06p+0.08(1600-p)=65 | | -14=2x-8 | | 144.54=2.55h+73.14 |